A multi-case study on the legitimacy construction of female successors in strategic innovation and green transition of petrochemical family enterprises - HU, Xueping (Edelweiss Applied Science and Technology, 2025)
This study investigates how female successors in family-owned petrochemical and high-carbon enterprises construct leadership legitimacy while promoting strategic innovation and green transformation. Drawing on legitimacy theory and institutional work, the research addresses a critical gap at the intersection of gender, family business succession, and environmental strategy. Through a qualitative multiple-case study of three female-led organizations—Hengli Group (China), Solvay (Belgium), and S.W. Jack Drilling Co. (United States)—the analysis reveals differentiated pathways of legitimacy construction across pragmatic, moral, and cognitive dimensions. The findings show that female successors deploy strategic narratives, institutional embedding, and stakeholder alignment to reconcile traditional family expectations with forward-looking environmental agendas. While gender remains a latent factor in leadership perception, legitimacy is often achieved through professional normalization and symbolic continuity rather than direct gender appeals. This study contributes to a deeper understanding of how gendered actors engage in institutional work within male-dominated legacy industries and offers theoretical and practical insights for succession planning, ESG leadership, and sustainable transformation in family enterprises.